2023
DOI: 10.1097/shk.0000000000002107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mesenchymal Stem Cells on Postresuscitation Renal and Intestinal Injuries in a Porcine Cardiac Arrest Model

Abstract: Objectives: Systemic ischemia-reperfusion triggered by cardiac arrest (CA) and resuscitation often causes postresuscitation multiple organ injuries. Mesenchymal stem cells (MSCs) have been proven to be a promising treatment for regional renal and intestinal ischemia reperfusion injuries. This study aimed to investigate the effects of MSCs on renal and intestinal injuries after cardiopulmonary resuscitation (CPR) in a porcine CA model. Methods: Twenty-two male pigs were randomly assigned to the sham (n = 6), CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, basic research has found that hypothermia can significantly improve the survival rate and neurological function and has a clear effect on oxidative stress, calcium homeostasis imbalance, and the opening of the mitochondrial permeability transition pore (44)(45)(46)(47)(48). In animal experiments, the type of cardiac arrest, the time of cooling, and the control of target temperature are relatively stable (49). For patients, the location of cardiac arrest, whether there were witnesses, the underlying disease, the category of cardiac arrest, age, and other factors, all have a complex impact on the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, basic research has found that hypothermia can significantly improve the survival rate and neurological function and has a clear effect on oxidative stress, calcium homeostasis imbalance, and the opening of the mitochondrial permeability transition pore (44)(45)(46)(47)(48). In animal experiments, the type of cardiac arrest, the time of cooling, and the control of target temperature are relatively stable (49). For patients, the location of cardiac arrest, whether there were witnesses, the underlying disease, the category of cardiac arrest, age, and other factors, all have a complex impact on the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%